IoT Monitoring System for Aquaculture Farming - Lim, Jia Hui; A Majid, Huda (Progress in Engineering Application and Technology, 2021)
In aquaculture breeding, the water quality is important to maintain the health of the aquatic along the farming period. Aquaculture monitoring procedures in Malaysia are currently inefficient as the farmers waste many time and costs to reduce the mortality of the aquatic in terms of human resources. The main objective of this project is to develop a wireless system which is Internet of Things (IoT) for remote monitoring aquaculture farming. Besides, the objective is to develop a water monitoring system android application for aquaculture farming and to study the proper habitat for freshwater prawn. The cloud the database system for the water condition and the surrounding condition is proposed. Arduino Uno, humidity sensors, waterproof temperature sensor and ultrasonic sensor are used to collect and send data. The data will be sent to cloud platform via wireless internet connection and can be viewed on android-based smartphone. The system can be improved by integrating an autonomous farming system.